Analysis of forces acting on the anchor-valve of a pneumatic solenoid valve - Yatsunskyi, Petro; Horbach, Nazar (Видавництво Львівської політехніки, 2025)
The article presents an analysis of the forces acting on the armature-valve of a pneumatic solenoid valve, which is a key element in pneumatic actuator control systems. The present study is an experimental and theoretical investigation into the influence of magnetic, pneumatic and inertial forces on the dynamics of armature movement. The findings of the analysis can be utilised to enhance the precision and efficacy of pulse collectors within intricate technical systems. The experimental study investigated the impact of variations in the distance between the armature and the magnetic circuit, in conjunction with changes in vacuum pressure, on the electromagnetic effort necessary to actuate the valve. The findings suggest that as the air gap and vacuum pressure increase, a significantly higher magnetomotive force is required to initiate valve movement. This finding indicates a non-linear relationship between the system’s pneumatic conditions and the electromagnetic force necessary for actuation.
Keywords: pulse collector; anchor valve; pneumatic solenoid; dynamics; magnetic forces; pneumatic forces; automation